Metal–Organic Framework Photosensitized TiO2 Co‐catalyst: A Facile Strategy to Achieve a High Efficiency Photocatalytic System. Issue 16 (20th February 2017) - Xie, Ming‐Hua; Shao, Rong; Xi, Xin‐Guo; Hou, Gui‐Hua; Guan, Rong‐Feng; Dong, Peng‐Yu; Zhang, Qin‐Fang; Yang, Xiu‐Li
Abstract: A 3D metal–organic framework (ADA‐Cd=[Cd2 L2 (DMF)2 ]⋅3 H2 O where H2 L is (2 E, 2′ E )‐3, 3′‐(anthracene‐9, 10‐diyl)diacrylic acid) constructed from diacrylate substituted anthracene, sharing structural characteristics with some frequently employed anthraquinone‐type dye sensitizers, was introduced as an effective sensitizer for anatase TiO2 to achieve enhanced visible light photocatalytic performance. A facile mechanical mixing procedure was adopted to prepare the co‐catalyst denoted as ADA‐Cd/TiO2, which showed enhanced photodegradation ability, as well as sustainability, towards several dyes under visible light irradiation. Mechanistic studies revealed that ADA‐Cd acted as the antenna to harvest visible light energy, generating excited electrons, which were injected to the conduction band (CB) of TiO2, facilitating the separation efficiency of charge carriers. As suggested by the results of control experiments, combined with the corresponding redox potential of possible oxidative species, . O2 −, generated from the oxygen of ambient air at the CB of TiO2 was believed to play a dominant role over . OH and h + . UV/Vis and photoluminescence technologies were adopted to monitor the generation of . O2 − and . OH, respectively. This work presents a facile strategy to achieve a visible light photocatalyst with enhanced catalytic activity and sustainability; the simplicity, efficiency, and stability of this strategy may provide a promising way to achieve environmental remediation. Abstract : To dye for : A 3D metal–organic framework constructed from an anthracene derivative was employed as an efficient sensitizer for anatase TiO2 . The co‐catalyst was prepared by mechanical mixing, which should be regarded as the simplest synthetic strategy in materials science. The co‐catalyst can efficiently photo‐eliminate organic dyes under visible light irradiation. Photodegradation experiments were carried out to study the possible mechanism.